Long-term effects of oxidative stress in volleyball players - Martinovic, J.; Dopsaj, V.; Dopsaj, M.; Kotur-Stevuljevic, J.; Vujovic, A.; Stefanovic, A.; Nesic, G. (International Journal of Sports Medicine, 2009)
The aim of this study was to determine the impact of long-term training on elite female volleyball players and to determine parameters that could discriminate them according to the level of oxidative stress-associated adaptation. Fifty-four elite female volleyball players were divided into 3 groups (1: below-average training experience <8.0 years, 2: average training experience between 8.0 and 10.5 years and 3: above-average training experience >10.5 years). The measured parameters were reactive oxygen metabolites, biological anti-oxidative potential, superoxide anion, malondialdehyde, advanced oxidation protein products, lipid hydroperoxides, paraoxonase activity, superoxide-dismutase activity and sulphydryl groups. Multiple discriminant analysis of the oxidative stress status parameters between the three groups of athletes indicated a statistically significant difference (Wilks' lambda=0.458, X2=35.898, p=0.031). The most important discriminant variables, superoxide-dismutase and superoxide anion, were the best indicators of differences between groups with different training experience. The significantly higher values were found in Group 3 compared with Group 1 in superoxide-dismutase activity (141±32 vs. 86±46; p=0.002), sulphydryl groups (p=0.031), and reactive oxygen metabolites (p=0.042). The significantly lower superoxide anion was found between Group 3 and Group 1 (377±187 vs. 1183±905; p=0.001). Oxidative stress status parameters adequately discriminated 68.5% of athletes with different training experience.